Potencial bio-combustible de la madera tostada y carbón de tres especies maderables de la parcela 2 del arboretum el huayo, Puerto Almendra, Loreto-Perú, 2017 - Chujutalli Galvez, Edgar Xavier (2018)
In the present study the potential yield of bio-fuel products was quantified toasted wood and standing charcoal from E. grandiflora, C. cateniformis and V. obovata from the plot 2 of the Arboretum "El Huayo" in Puerto Almendra. The samples for the calculation of the potential yield of the standing trees were made by means of a forest census from the 25 cm diameter of the DBH of the species E. grandifolia, C. cateniformis and V. obovata of plot 2 of the arboretum "El Huayo"; and with allometric formulae the tree volume was determined and with data obtained in the laboratory for yields in toasted wood and coal of these species, the potential yield in kilograms was calculated. The results show that the highest bio-fuel yield in toasted wood was in E. grandiflora with 2 011,3 kg/tree, followed by C. cateniformis with 1 072,3 kg/tree, while V. obovata is the one with the lowest yield 435,8 kg/tree. Coal was 1 070,4 kg/tree, 504,6 kg/tree and 200,9 kg/tree respectively. While the highest potential yield in roasted wood per hectare was determined in E. grandifolia with 54 304,0 kg/ha and in coal with 28 900,5 kg/ha.